2012
DOI: 10.3390/admsci2010082
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Entrepreneurship Education for College Students in China

Abstract: Partly as a result of the rapid growth in Chinese higher education, graduate placement has become a critical issue facing colleges and universties. In response, one of the policy initiatives adopted by the Chinese government is for higher education institutions to put an emphasis on entrepreneurship education. In 2002, the Ministry of Education launched a pilot program on carrying out entrepreneurship education in nine prestigious higher education institutions in China. Since then, many colleges and universiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 7 publications
1
48
0
2
Order By: Relevance
“…The results obtained from students' responses showed that most or generally students gave a positive response to bioentrepreneurship learning using comics. Zhou and Xu (2012) argued that learning entrepreneurship could be used as a recommendation for improving living standards in the future.…”
Section: %mentioning
confidence: 99%
“…The results obtained from students' responses showed that most or generally students gave a positive response to bioentrepreneurship learning using comics. Zhou and Xu (2012) argued that learning entrepreneurship could be used as a recommendation for improving living standards in the future.…”
Section: %mentioning
confidence: 99%
“…Entrepreneurship education itself, as said by Zhou and Xu (2012), was introduced by the United States in 1940s. Then entrepreneurship education was adopted in many countries for fostering job creation.…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
“…In developing countries, China is paying more and more attention to the innovation and entrepreneurship education. A lot of scholars have carried out the relevant research [8,9,17]. For example, Wu [17] expounded the necessity to build a new system of entrepreneurship education in colleges and universities to, after the analysis of the related concepts of innovation and entrepreneurship education.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, both the development of national economy and the career planning of college students have the realistic need for innovation and entrepreneurship education. In view of the current severe employment situation in China, the government has introduced a number of policies to support innovation and entrepreneurship development of college students [8,9]. More and more students of business administration major desire to accept entrepreneurial skills training and exercise the business combat skills as early as possible during the period of school [3,8,10].…”
Section: Introductionmentioning
confidence: 99%